Percussion Creations Bebarongan Metsis | Tabuh Kreasi Bebarongan Metsis - I Made Agus Wisnu Tenaya Surjana (GHURNITA: Jurnal Seni Karawitan, 2024)
Metsis' Bebarongan percussion creation is a musical work inspired by a phenomenon in butterflies called metamorphosis. Metamorphosis is a phenomenon that occurs in the life of butterflies from eggs, larvae, pupae, and amigo. The medium of expression used in Metsis' work is the Barungan gamelan Gong Kebyar. The creation method used in Metsis' work is the Panca Sthiti Ngawi Sani method from Balinese artist I Wayan Dibia, which contains five stages, namely: Inspiration Stage, Exportation Stage, Conception Stage, Execution Stage, and Ngebah Stage. This work uses a section structure with four parts, each describing a metamorphosis process. Parts 1. Describe an egg, 2. Describe a caterpillar; 3. Describe a cocoon, and 4. Describe the successful process of metamorphosis from an egg to a butterfly.